2015
DOI: 10.1016/j.ijhydene.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen induced amorphization of LaMgNi4 phase in metal hydride alloys

Abstract: Available online xxxKeywords: Hydrogen absorbing alloys Hydrogen induced amorphization Metal hydride electrode Transmission electron microscope Re-crystallization a b s t r a c t Hydrogen induced amorphization (HIA) of the LaMgNi 4 phase at 30 C was found in three LaMgNi 4 /LaNi 5 two-phase metal hydride (MH)-forming alloys. The amorphizationhappened at the first dehydrogenation cycle from a fully hydrided alloy, and the process is reversible after annealing at 250 C for 1 h. The hydrogen storage capacity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that by performing multiple substitutions of both the A element, and the B elements, the stability of the structure during cycling and storage capacities are affected [12][13][14][15]. It has been found that by substituting Mg for La in rareearth (RE) superlattice based A 2 B 7 -type metal hydrides, it is possible to achieve a higher storage capacity (compared to commercial AB 5 -type alloys), a lower self-discharge if used in batteries and improved cycle stability by preventing the occurrence of hydrogen-induced amorphization (HIA), when compared to pure La 2 Ni 7 [12,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that by performing multiple substitutions of both the A element, and the B elements, the stability of the structure during cycling and storage capacities are affected [12][13][14][15]. It has been found that by substituting Mg for La in rareearth (RE) superlattice based A 2 B 7 -type metal hydrides, it is possible to achieve a higher storage capacity (compared to commercial AB 5 -type alloys), a lower self-discharge if used in batteries and improved cycle stability by preventing the occurrence of hydrogen-induced amorphization (HIA), when compared to pure La 2 Ni 7 [12,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%